Augmented reality in engineering education: enhancing learning and application - Suhail, Nasija; Bahroun, Zied; Ahmed, Vian (Frontiers in Virtual Reality, 2024)
Introduction: Augmented Reality (AR) is a transformative technology that enhances teaching and learning by blending virtual and real environments. While AR's potential to improve visualization, interaction, and student engagement in engineering education is recognized, its application across various engineering disciplines remains underexplored. This study systematically investigates AR's use in engineering fields, highlighting its educational impact and identifying gaps for future research. Methods: A systematic review was conducted using the PRISMA framework, analyzing 67 peer-reviewed papers on AR in engineering education. Content analysis was employed to assess AR's effectiveness in enhancing visualization, interaction, and motivation. A bibliometric analysis identified key AR tools, research trends, geographic distribution, and interdisciplinary collaboration. Results: AR is extensively applied in civil and mechanical engineering, where tools like Unity 3D significantly improve visualization and interaction. AR enhances student engagement and comprehension, particularly in complex areas like construction design. However, its adoption in other engineering disciplines remains limited. The analysis also shows AR’s positive impact on motivation and learning outcomes, despite challenges such as technical limitations and insufficient training for educators. Conclusion: Although AR is gaining traction in engineering education, broader adoption is hindered by technical challenges and the need for better curriculum integration. Future research should address these barriers and explore AR’s potential in underutilized engineering disciplines to maximize its educational benefits.